An improved strategy to support multiple QoS assessment for selecting content adaptation services - Mohamed, Juliana (2015)
Content adaptation is a solution in providing ubiquitous access of the increasingly rich Internet multimedia contents (i.e., resources) to a variety of users’ requirement, along with their limited device’s capability (i.e., delivery contexts). Service Oriented Content Adaptation (SOCA) framework enables users to use content adaptation services on pay-as-you-go basis, thus demanding for a good quality of service (QoS). One of the important QoS criteria is the maximum time that a user can wait (i.e., response time) for the output to be displayed. The service provider offers one waiting time (QoS) during the advertisement, based on the fair load. However, the advertised waiting time may not be deliverable accordingly during the actual service execution due to a heavy load. Practically, the service provider should be able to estimate a current deliverable response time before the Service Level Agreement (SLA) settled. With the purpose of overcoming these constraints, this thesis will be focusing on providing an improved strategy, called one-to-multiple assessment strategy for SOCA framework, that focuses on assessing current waiting time and evaluate its deliverability. The purpose of SLA assessor is to consider the current QoS (server load) of other services negotiated for the other interrelated tasks. This is performed by a function called a checker. In conclusion, the SLA assessor improves the SLA settlement rate between users and content adaptation services. Also, it reduces the extra overhead (i.e., communication step) to reconsidering another service for a particular task compared to the existing one-to-one assessment strategy.